1998
DOI: 10.1021/bi9727996
|View full text |Cite
|
Sign up to set email alerts
|

Role of the [4Fe-4S] Cluster in Reductive Activation of the Cobalt Center of the Corrinoid Iron−Sulfur Protein from Clostridium thermoaceticum during Acetate Biosynthesis

Abstract: The corrinoid iron-sulfur protein (CFeSP) from Clostridium thermoaceticum functions as a methyl carrier in the Wood-Ljungdahl pathway of acetyl-CoA synthesis. The small subunit (33 kDa) contains cobalt in a corrinoid cofactor, and the large subunit (55 kDa) contains a [4Fe-4S] cluster. The cobalt center is methylated by methyltetrahydrofolate (CH3-H4folate) to form a methylcobalt intermediate and, subsequently, is demethylated by carbon monoxide dehydrogenase/acetyl-CoA synthase (CODH/ACS). The work described … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 60 publications
6
76
0
Order By: Relevance
“…9, the next step is attack by Ni(I) on the methyl group of methylcob(III)amide (bound to the corrinoid iron-sulfur component of the complex) to form methyl-Ni(III) (Reaction 5). Recent results strongly indicate that this methyl transfer is a nucleophilic displacement, not a radical, reaction (46,48). We propose that it is the next step at which the CODH subunit is required.…”
Section: Figmentioning
confidence: 72%
“…9, the next step is attack by Ni(I) on the methyl group of methylcob(III)amide (bound to the corrinoid iron-sulfur component of the complex) to form methyl-Ni(III) (Reaction 5). Recent results strongly indicate that this methyl transfer is a nucleophilic displacement, not a radical, reaction (46,48). We propose that it is the next step at which the CODH subunit is required.…”
Section: Figmentioning
confidence: 72%
“…The physiological role of the [4Fe4S] cluster of CoFeSP is enigmatic, as it does not directly contribute to the chemistry of methyl transfer neither from methyltransferase to CoFeSP nor from CoFeSP to acetyl-CoA synthase. It was suggested that the [4Fe4S] cluster was essential for the communication between CoFeSP and physiological electron donors providing a conduit for electron flow from, for example, CO-reduced carbon monoxide dehydrogenase or a ferredoxin to the cobalamin 13,14 . In the RACo:CoFeSP complex, the [4Fe4S] cluster domain of CoFeSP interacts extensively with the RACo dimer ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The absence of protein ligands is the probable reason why the redox potential of the Co 2þ ∕Co 1þ couple of CoFeSP is about 50-100 mV more positive than in other corrinoid containing methyltransferases (25,33), rendering it reducible by electrons generated from the oxidation of CO by carbon monoxide dehydrogenases (26). The necessity for an ATP-dependent reductive activator has therefore not been anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…The occasional oxidation of Co(I) to Co(II) inactivates CoFeSP, which has to be reactivated by a one-electron reduction (23,24). The low midpoint potential needed to reduce Co 2þ to Co 1þ (< − 504 mV at pH 7.4) (25) can be achieved in vitro using either chemical reducing agents such as Na-dithionite (DT), Ti 3þ citrate, via photoreduction with deazariboflavin as a catalyst or enzymatically with electrons generated by the oxidation of CO to CO 2 by carbon monoxide dehydrogenase (22,26). An ATP-dependent reactivation of CoFeSP has not been reported so far.…”
mentioning
confidence: 99%